Media, persuasion and propaganda - Soules, Marshall (Media topics., 2015)
Using case studies and exercises, this innovative study poses challenging questions Living in a saturated media environment, we are crowded from all sides by persuasive messages and information. Advice, promotion and propaganda form a spectrum of persuasion - and everywhere we see it performed in its full theatricality, complete with actors, scripts, props and costumes. Based on enduring rhetorical principles, these persuasive techniques and the psychology behind them have become increasingly sophisticated during the 'age of persuasion', a century of applied research in advertising, advocacy, public relations, mass entertainment and social control. Media, Persuasion, and Propaganda guides the reader through the many varieties of persuasion and its performance, exploring the protocols of rhetoric unique to the medium, from orality and print to film and digital images. Using case studies and exercises, this innovative study poses challenging questions: How do individuals and organisations exert influence to build communities and networks? What role do media play in communicating persuasive messages? How do we use recent discoveries in cognitive science to promote a cause, advocate social change or market ideas and products? How do we defend ourselves against manipulation and undue influence, and when does persuasion turn into propaganda? Key Features Uses global examples and case studies to define the spectrum of persuasion, from promotion to propaganda Examines the performance of propaganda, from orality to new media Includes exercises in each chapter to reinforce the key themes and promote discussion